(untitled) (Research, Society and Development, 2021)
In the current world economical conjecture, the accentuated growth in Brazilian production and exportation in the Agro-Food industry sets the country as a central role in the field. Implementing storage units in Agricole properties and industrial sites constitutes a necessary premise to keep the country as a competitive member in the global scenery. The vertical silos present themselves as alternative solutions. However, a great sum of the existent silos does not match the ideal conditions of operation due to the insufficient knowledge of the pressure variations that happen in time and inner space, of the flow, and the variables that affect the behavior of the stored products. Such situations have contributed to accidents and breakdowns in silos. With this increasing demand for the storage capacity in silos, the full understanding of the structural functioning, failure prevention, and optimization of the structural components became of great importance. Thus, this work aimed to present some events that happened in the country in the last years and bring the main causes of structural failures, highlighting the failures that are directly related to the type of flow in the interior of the silo; wacky charging and/or discharging; change in the properties of the stored products (specified weight, actual inner friction angle, friction angle against the wall) and instability in the support columns. It follows that a great number of accidents in these structures could have been avoided or reduced with previous knowledge, from the silo designer and those responsible for the operation, about the most important occurrences in silos.